Development of Digital Mathematics Teaching Materials Based on a Self-Regulated Learning Approach to Increase the Creativity of Jakarta Teachers - Flavia Aurelia Hidajat (Asosiasi Dosen Pengembang Masyarajat (ADPEMAS) Forum Komunikasi Dosen Peneliti, 2023)
The creativity of teachers in developing digital mathematics teaching materials is required to increase students' understanding independently in online learning. A good learning strategy to increase creativity and independent learning is self-regulated learning. This community service training aims to increase the creativity of Jakarta teachers in developing teaching materials for digital mathematics learning based on a self-regulated learning approach. Twenty-three high school teachers in Jakarta attended the training. The stages consist of pre-training, training process, and post-training. The results of this community service training. The results show that: The teachers understand the material about the systematic development of digital mathematical teaching materials; Training provides clear information; The output of the training can help the learning of teachers; Teachers' creativity is increasing by making mathematics digital teaching material based on self-regulated learning Approach as the output of this training.